2011
DOI: 10.1073/pnas.1107740108
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Pragmin regulates Src family kinases via the Glu-Pro-Ile-Tyr-Ala (EPIYA) motif that is exploited by bacterial effectors

Abstract: Several pathogenic bacteria have adopted effector proteins that, upon delivery into mammalian cells, undergo tyrosine phosphorylation at the Glu-Pro-Ile-Tyr-Ala (EPIYA) or EPIYA-like sequence motif by host kinases such as Src family kinases (SFKs). This EPIYA phosphorylation triggers complex formation of bacterial effectors with SH2 domain-containing proteins that results in perturbation of host cell signaling and subsequent pathogenesis. Although the presence of such an anomalous protein interaction suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 33 publications
5
91
0
3
Order By: Relevance
“…Herein we report the identification of a novel binding partner of the Notch transcriptional activation complex, which we termed NACK. This protein has been previously identified as Pragmin and has been shown to interact with Rho family GTPases (27) and C-terminal Src kinase (28). Using both in vivo and in vitro approaches we demonstrated that NACK acts as a regulator of Notch transcription, is necessary for Notch-driven tumorigenesis, and is required for embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Herein we report the identification of a novel binding partner of the Notch transcriptional activation complex, which we termed NACK. This protein has been previously identified as Pragmin and has been shown to interact with Rho family GTPases (27) and C-terminal Src kinase (28). Using both in vivo and in vitro approaches we demonstrated that NACK acts as a regulator of Notch transcription, is necessary for Notch-driven tumorigenesis, and is required for embryonic development.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, Safari et al reported that in the presence of CagA H. pylori, the amount of CSK /Pragmin interaction was reduced. In fact, they found the competition between CagA and Pragmin to interact with CSK in tyrosine phosphorylation manner at EPIYA motif (19). Of note, it was demonstrated that CagA/CSK interaction occurs at plasma membrane, whereas Pragmin interact with CSK at cytoplasm, and thereby the possible mechanisms that are involved in related downstream molecules to induce elongated cells may also be different.…”
Section: Discussionmentioning
confidence: 99%
“…After tyrosine phosphorylation at EPIYA motif, Pragmin can interact with CSK. Interestingly, it was found that the cells with high expression of Pragmin have the elongated morphology that contributes to tumor invasion and metastasis (19)(20)(21). In this regard, it was shown that ectopic expression of Pragmin in human pancreatic duct epithelial (PDAC) cells induced an elongated mesenchymal-like cell morphology, which is associated with increased cell migration and invasion (22).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogen mimics are widely distributed across the tree of life, including proteobacteria, spirochaetes, firmicutes, fungi, chromalveolata, excavata and animalia [2 , [9][10][11]. Similar to viruses, these linear motif mimics have contributed to the discovery of new host linear motifs [12] and mediate a wide range of processes, such as adhesion to target cells, virulence protein secretion, perturbation of cell signaling, and inhibition of host defense systems [2 ,9]. Despite the growing recognition of their relevance, we are only beginning to understand the evolutionary patterns and comparative properties of host motifs and their pathogen mimics.…”
Section: Introductionmentioning
confidence: 99%